Friedel–Crafts reaction of indoles for (3-indolyl)methyl ethers under basic condition: Application in unsymmetrical bis(indolyl)methanes - Zubiao Zheng (Elsevier, 2021)
An efficient process to prepare (3-indolyl)methyl ethers from various indoles and benzaldehydes under basic conditions was reported. The effects of bases, solvents were investigated. Under the optimal condition, most of (3-indolyl)methyl ethers were obtained in 90–98% yields. The utility of the (3-indolyl)methyl ethers was further demonstrated to successfully produce unsymmetrical bis(indolyl) methanes(BIMs) with good yields.